Interacting with virtual objects via embodied avatar hands reduces pain intensity and diverts attention - Hunter G. Hoffman (Nature Portfolio, 2021)
Abstract The current study introduces a new paradigm for exploring cognitive factors in pain. Interacting with virtual objects via embodied avatar hands increased the illusion of “being there” in the virtual world, increased VR analgesia for acute pain, and reduced accuracy on an attention demanding task. Twenty-four healthy volunteer college students participated in this within-subject randomized crossover design study. During Phase 1, each participant received brief thermal pain stimuli during interactive embodied avatar VR vs. passive VR (no avatar and no interactivity), VR treatment order randomized. After each pain stimulus, participants provided subjective 0–10 ratings of pain. Compared to the passive VR condition, during the interactive avatar VR, participants reported significant reductions in (1) worst pain, (2) pain unpleasantness, (3) time thinking about pain and (4). they had significantly more fun during the pain stimulus (p = .000 for each). During Phase 2, participants performed a divided attention task in each of the two VR conditions. Participants made significantly more errors on the divided attention task during the interactive avatar VR condition, compared to passive VR, implicating an attention mechanism for how virtual reality reduces pain and helping understand how VR influences pain perception. Trial registration: NCT04245475. Date of registration: 29/01/2020.